(untitled) (E Global Congress, 2024)
The fact that there is a high level of competition in the world market of thread and yarn shows the need for the creation of modern, automated techniques and technologies that allow rapid changes in the quality, quantity and assortment of products. In this regard, by radically improving the quality indicators of spun yarns, at the same time, creating effective systems for increasing the quality and competitiveness of spun yarns, by developing high-efficiency equipment, control and measurement tools and technologies at spinning enterprises, and by improving the constructions of spinning machines. Implementation of targeted scientific research in areas such as product quality improvement is considered one of the urgent tasks